Pembiayaan Pendidikan pada Masa Pandemi Covid-19 (Studi Kasus di Pondok Pesantren Al-Ma’arif Assa’adiyah Payakumbuh - Eci Sriwahyuni (J-STAF: Siddiq, Tabligh, Amanah, Fathonah, 2022)
This study aims to find out how the financing of education at the Al-Ma'arif Assa'adiyah Islamic boarding school during the covid-19 pandemic until now. Since the pandemic began to affect economic factors, since then the education funding sourced from the parents of students began to decline. On the other hand, school operational financing must run because the teaching and learning process continues both online and offline. This research is qualitative in nature with the key informant being the head of the Islamic boarding school and the supporting informants are the chairman of the foundation, deputy principal, teachers and students of the Payakumbuh Al-Ma'arif Islamic boarding school. In collecting data, observation, interview, and documentation techniques were used. The data analysis technique in this study consisted of three components of data analysis, namely data reduction, data presentation, and drawing conclusions. The results showed that several efforts were made by the school principal along with other related elements in helping to finance education during the pandemic, namely: (1) Opening a small and medium-sized business consisting of a laundry business, rendang telur and chips business which was marketed locally and also outside the region, business in agriculture by growing chili and breeding vanilla seeds; (2) Building good relations with the community and expanding the network by building good relations with alumni, recruiting permanent and non-permanent donors and carrying out proposals for assistance through friendship.